(untitled) (Journal of the College of Basic Education, 2023)
Varying sentence length and patterns results in a natural , fluid form ofwriting . Writing should be pleasing to readers . If all of the sentences follow thesame pattern , however , the writing and rhythm become boring and dull .Creating a variety of sentence patterns not only holds a reader’s interest , which ,after all , is the purpose of writing , but it also reflects the mind’s ability to thinkcreatively and complexly . There are many options to change the simplesentences into more sophisticated sentences . Therefore , this paper is devoted toanalyzes the main marked structures of fronting and postposing in Hard Times;written by Charles Dickens in 1854.These structures are passive voice , left-dislocation , cleft sentences , Extraposition , existential sentences , pseudo-cleftsentences , and reversed — pseudo cleft sentences .It aims at discovering thestylistic realization of these structures and their coincidence with the importantevents in the novel, especially certain specific communicative implications canbe revealed by these structures. So instead of having chosen independentexamples coming from a computational corpus , we decide to analyze thesestructures in a novel written by Charles Dickens . With the analysis of thecorpus of examples, it will be proved that the use of these anomalous syntacticprocesses points out a clear contrast with the normal order of the Englishsentence i.e., these syntactic processes clearly break SVO